The burgeoning HIV/HCV syndemic in the urban Northeast: HCV, HIV, and HIV/HCV coinfection in an urban setting. - Morano, Jamie P; Gibson, Britton A; Altice, Frederick L (PloS one, 2013)
Despite recommendations for generation-based HCV and once lifetime HIV screening, thousands of individuals in the U.S. still remain untested and undiagnosed. This cross-sectional study examines the correlates of HCV and HIV monoinfection and HIV/HCV coinfection in an urban Northeast setting.
Keywords: Adult; Cities; Coinfection; Epidemics; Female; Hepatitis C; HIV Infections; Humans; Logistic Models; Male; Middle Aged; New England